Xenogeneic-free generation of vascular smooth muscle cells from human induced pluripotent stem cells for vascular tissue engineering. (1st January 2021) - Luo, Jiesi; Lin, Yuyao; Shi, Xiangyu; Li, Guangxin; Kural, Mehmet H.; Anderson, Christopher W.; Ellis, Matthew W.; Riaz, Muhammad; Tellides, George; Niklason, Laura E.; Qyang, Yibing
Abstract: Development of mechanically advanced tissue-engineered vascular grafts (TEVGs) from human induced pluripotent stem cell (hiPSC)-derived vascular smooth muscle cells (hiPSC-VSMCs) offers an innovative approach to replace or bypass diseased blood vessels. To move current hiPSC-TEVGs toward clinical application, it is essential to obtain hiPSC-VSMC-derived tissues under xenogeneic-free conditions, meaning without the use of any animal-derived reagents. Many approaches in VSMC differentiation of hiPSCs have been reported, although a xenogeneic-free method for generating hiPSC-VSMCs suitable for vascular tissue engineering has yet to be established. Based on our previously established standard method of xenogeneic VSMC differentiation, we have replaced all animal-derived reagents with functional counterparts of human origin and successfully derived functional xenogeneic-free hiPSC-VSMCs (XF-hiPSC-VSMCs). Next, our group developed tissue rings via cellular self-assembly from XF-hiPSC-VSMCs, which exhibited comparable mechanical strength to those developed from xenogeneic hiPSC-VSMCs. Moreover, by seeding XF-hiPSC-VSMCs onto biodegradable polyglycolic acid (PGA) scaffolds, we generated engineered vascular tissues presenting effective collagen deposition which were suitable for implantation into an immunodeficient mice model. In conclusion, our xenogeneic-free conditions for generating hiPSC-VSMCs produce cells with the comparable capacity for vascular tissue engineering as standard xenogeneic protocols, thereby moving the hiPSC-TEVG technology one step closer to safe and efficacious clinical translation. Graphical abstract: Image, graphical abstract